Assessing the contributions of site and species to plant beta diversity in alpine grassland ecosystems - Jie Li; Xiao Pan Pang; Zheng Gang Guo (Plant Diversity)
Understanding plant diversity within geographical ranges and identifying key species that drive community variation can provide crucial insights for the management of grasslands. However, the contribution of both local sites and plant species to beta diversity in grassland ecosystems has yet to be accurately assessed. This study applied the ecological uniqueness approach to examine both local contributions to beta diversity (LCBD) and species contributions to beta diversity (SCBD) across six major geographical ranges in alpine grasslands. We found that LCBD was driven by species turnover, with climate, plant communities, and their interactions influencing LCBD across spatial scales. LCBD values were high in areas with low evapotranspiration, high rainfall variability, and low species and functional richness. Precipitation seasonality predicted large-scale LCBD dynamics, while plant community abundance explained local LCBD variation. In addition, we found that SCBD were confined to species with moderate occupancy, although these species contributed less to plant biological traits. Our findings are crucial for understanding how ecological characteristics influence plant beta diversity in grasslands and how it responds to environmental and community factors. In addition, these findings have successfully identified key sites and priority plants for conservation, indicating that using standardized quadrats can support the assessment of the ecological uniqueness in grassland ecosystems. We hope these insights will inform the development of conservation strategies, thereby supporting regional plant diversity and resisting vegetation homogenization.